2020
DOI: 10.3390/molecules25092061
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on NMR Spectroscopy of 2,2-Dimethylchroman-4-one Derivatives: Experimental and Theoretical Studies

Abstract: The attribution of 1H and 13C NMR signals of a library of 5-, 6- and 7-substituted 2,2-dimethylchroman-4-one derivatives is reported. Substituent effects were interpreted in terms of the Hammett equation, showing a good correlation for carbons para- to the substituent group, not for the meta- ones. Similarly, the Lynch correlation shows the additivity of the substituent chemical shifts in the case of both H and C nuclei, again with the exception of the carbons in the meta- position. Density Functional Theory (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In general, Hammett’s substituent constant determines the relative electronic effects of any given substituents on the electron density of the reaction center under consideration . Numerous studies suggested that Hammett parameters can be correlated with the NMR chemical shift values. Accordingly, the chemical shift values of N–H protons of indole ( 1a ), 3-Me-indole ( 1b ), indole 3-carboxaldehyde ( 1d ), and 3-cyano indole ( 1c ) (from their 1 H NMR spectra) were compared with their initial rate of N–H insertion to the phenyl diazoester. It was observed that the more electron-donating the C3 substituent (of the indole) is, the more upfield the N–H protons are and consequently the slower is the rate of the reaction [Figure A].…”
Section: Resultsmentioning
confidence: 99%
“…In general, Hammett’s substituent constant determines the relative electronic effects of any given substituents on the electron density of the reaction center under consideration . Numerous studies suggested that Hammett parameters can be correlated with the NMR chemical shift values. Accordingly, the chemical shift values of N–H protons of indole ( 1a ), 3-Me-indole ( 1b ), indole 3-carboxaldehyde ( 1d ), and 3-cyano indole ( 1c ) (from their 1 H NMR spectra) were compared with their initial rate of N–H insertion to the phenyl diazoester. It was observed that the more electron-donating the C3 substituent (of the indole) is, the more upfield the N–H protons are and consequently the slower is the rate of the reaction [Figure A].…”
Section: Resultsmentioning
confidence: 99%
“…Hammett proposed his theory long ago from experimental observations 18,19 resting on the idea that the electron‐donating or electron‐withdrawing power of a substituent in an aromatic molecule can be quantified and the corresponding values of the Hammett's constants used in any type of these systems. This original idea and its extensions afterward have provided the basis for the quantitative rationalization of structure‐reactivity in organic chemistry 21 and a plethora of other chemical phenomena ranging from RMN effects, 26 characterizations of different catalytic of Au nanoparticles on different supports, 27 metal–organic frameworks (MOFs), 28 non‐covalent interactions, 29 and photophysical properties of dyes, 30 among others. In this work, we use HT to explore correlations between optoelectronic properties and device parameters of the DPPs.…”
Section: Theoretical and Computational Methodsmentioning
confidence: 99%
“…These relationships are frequently mentioned as linear free-energy relationships (LFER). The LFER has often been used to cover the whole correlation study in organic chemistry [1][2][3]. Modern studies show that Hammett parameters can be correlated with the reaction rates, equilibrium constants, IR frequencies, UV absorption and NMR chemical shifts [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%